Quantification of geopolymers production by chemical methods- A short review - Siyal, A.A. (American Institute of Physics Inc., 2015)
Inorganic polymers are the aluminosilicate materials possessing properties superior than ordinary Portland cement. In this review paper the chemical techniques used for determining degree of reaction of fly ash or the quantity of geopolymer material produced have been discussed. These methods determine the amount of product formed in percentages. The methods include HCl method, salicylic acid method, and picric acid method. These methods are not only used for fly ash but they are being used for determining the degree of reactions of metakaolin and other pozzolanic materials. The picric acid is an explosive material and its transportation in high concentration is dangerous. During its use in laboratory there is also the risk of fire associated with it. According to the microscopic analysis results the picric acid attack dissolves small amount of fine unreacted fly ash particles also. The salicylic acid is easily available but the residue from its treatment contains unreacted fly ash particles, hydration phases, and certain parts of unreacted OPC. The residue from HCl and salicylic acid attack contains MgO particles which is the part of the hydration product. The HCl method is mostly used due to simple process and lower standard deviation. Â© 2015 AIP Publishing LLC.